Do Native Speakers in Youtube Videos Benefit EFL Students’ Phonological Appropriation? - Marwa Marwa; Herdi Herdi (Lectura : Jurnal Pendidikan, 2017)
This classroom action research investigates how YouTube videos containingpronunciation drills exposed by English native speakers develop the EFL students’phonological appropriation. This activity also relates to developing classroom-basedmaterials via accessing various relevant resources inside and outside the classroom asthey are available in the information, communication and technology (ICT) era now.The study was based on the problems that the students got difficulties in EnglishPhonology class pertaining to the segmental, supra-segmental phonemes andphonological contrast. It is all about the phonology complex rules that students have tounderstand and drill in a very short meeting hour (2 credits course- 2x45 minutes permeeting). The participants of the study were the fourth semester students (class F) ofEnglish Education Department of Faculty of Education, Lancang Kuning University inRiau. The study was conducted from March to May 2014 only in one cycle consisting ofseven meetings. The study reveals that using such YouTube videos could improvestudents’ phonological appropriation and assist them in understanding the complex rulesof English phonology class since they had been experienced with English nativespeakersas the models for their pronunciation learning and practices as they couldaccess them in YouTube.